Stylistic Study of the Late Mesolithic Industries in Western France: Combined Principal Coordinate Analysis and Use-Wear Analysis - Hauguel-Bleuven, Lola; Calvo-Gómez, Jorge; Marchand, Gregor (Open archaeology (Berlin, Germany), 2023)
The notion of style has been the subject of much research and theoretical development in prehistoric archaeology. This vast concept touches several fields, including the morphology of artefacts, technical gestures and their function. The lithic typology of arrowhead armatures was widely developed in the twentieth century for the study of the French Mesolithic and includes some of these aspects. The functional, technical, or aesthetic nature of the morphological characteristics of these artefacts has received little attention, while the mapping of types has been overvalued This article presents a new approach combining statistical analysis with the use-wear analysis of arrowhead from several Breton sites, dated to the Late Mesolithic.